Submissão Feminina no Romance A Vida em Flor de Dona Bêja a Partir da Personagem Maria - Amarante Nascimento, Vinícius; Aparecida Ribeiro Lopes de Almeida, Edwirgens (Journal of Literature, History and Memory, 2024)
ABSTRACT: In the 1957 novel written by Agripa Vasconcelos, A vida em flor de Dona Bêja, which represents the cycle of the settlement of the state of Minas Gerais in the 19th century, Dona Beja is the female figure in the story of Araxá who stars in the novel. However, this research aimed to analyze the representations created about the mother of Dona Beja, the character Maria, because, from her participation in the plot of the novel, it is possible to rethink the female situation in the patriarchal society and perceive the attempt of male domination over women. expressed through various forms of violence. In this way, it is possible to affirm that, from a historical fiction, it is possible to rethink the inequalities that have been constituted throughout history between men and women.